(untitled) (UNIZIK Journal of Agricultural Economics and Extension, 2024)
The ability of smallholder farmers to adapt to climate change hinges on their financial resources. The main objective of this study was to investigate the influence of financial inclusion on the adoption of climate change adaptation strategies among smallholder farmers in Oyo State, Nigeria. Using a well-structured questionnaire, primary data were collected from 170 randomly selected respondents through a multistage sampling technique. Analysis of the data was conducted using descriptive statistics alongside the Multivariate Probit (MVP) model. The descriptive statistics unveiled that smallholder farmers employed a variety of adaptation measures to mitigate the detrimental impacts of climate change on their agricultural activities. Techniques such as soil and water conservation, cultivation of drought and heat-resistant crop varieties and mixed cropping emerged as the most utilised adaptation options in the study area. The results from the MVP model indicated that the socio-economic characteristics, including age, gender, marital status, education, household size, cultivated land area, farming experience, access to extension services, total income, of the smallholder farmers as well as financial inclusion indicators including credit accessibility, and bank account ownership have a significant influence on their decision to adopt any of the adaptation strategies. Based on these findings, the study recommends that farmers be educated about the importance of having a bank account and calls for the attention of relevant stakeholders to facilitate the availability and accessibility of credit to smallholder farmers to enhance their ability to adapt to the rapidly changing change.